2020
DOI: 10.1101/2020.05.15.098855
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatiotemporal Evaluation of The Human Footprint in Colombia: Four Decades of Anthropic Impact in Highly Biodiverse Ecosystems

Abstract: 19The maintenance of biodiversity and the capacity of natural systems to provide goods and 20 services for people is affected on different levels by the intensity of human activities on 21 ecosystems. In this study, we apply a Legacy-adjusted Human Footprint Index (LHFI) to 22 evaluate the spatiotemporal variation of anthropic impact in Colombia in 1970, 1990, 2000 23 and 2015. We identified hotspots of change in LHFI and we evaluated the intensity of 24 anthropic pressures in natural regions and ecosystems. W… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 60 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…Our observations agree with previous records showing that L. tigrinus can live in proximity to human dominated landscapes (Escobar-Lasso et al 2014, Arias-Alzate 2014, Delgado-V 2009Delgado-V , 2014Liévano & López-Arévalo 2014, Jimenez-Alvarado et al 2017, Pineda Guerrero 2018. The records shown in Figure 1 indicate that L. tigrinus is occupying mainly the Andean region, which is one of the areas of the country that is most populated and with the highest human footprint (Correa Ayram et al 2020). The new observations reported herein are less than 9 km in a straight line from downtown Bucaramanga (Santander) extending the species range in Santander more than 111 km to the North-West of the nearest confirmed locality in Encino (Figure 1).…”
mentioning
confidence: 61%
“…Our observations agree with previous records showing that L. tigrinus can live in proximity to human dominated landscapes (Escobar-Lasso et al 2014, Arias-Alzate 2014, Delgado-V 2009Delgado-V , 2014Liévano & López-Arévalo 2014, Jimenez-Alvarado et al 2017, Pineda Guerrero 2018. The records shown in Figure 1 indicate that L. tigrinus is occupying mainly the Andean region, which is one of the areas of the country that is most populated and with the highest human footprint (Correa Ayram et al 2020). The new observations reported herein are less than 9 km in a straight line from downtown Bucaramanga (Santander) extending the species range in Santander more than 111 km to the North-West of the nearest confirmed locality in Encino (Figure 1).…”
mentioning
confidence: 61%
“…Key regions and ecosystems with a higher richness of listed migrants Within the focal area for migrants, all four resident groups had high threatened species richness along the western slope of the Andes of southern Colombia and northern Ecuador. This region is recognized for high biodiversity and endemism (Hof et al, 2011;Pimm et al, 2014) but has also experienced extensive impact in some areas (Correa Ayram et al, 2020); this combination of high biodiversity and impact underlies why this region featured so prominently in our analysis. Some regions of the Western Andes in Colombia receive de facto protection through the presence of indigenous reserves and Afro-Colombian territories, as well as the Reserva Forestal del Pacifico, but since the signing of a peace deal in 2016 between the Colombian government and the FARC, the region has been increasingly threatened by unregulated economic activities that result in deforestation (Prem et al, 2020).…”
Section: Discussionmentioning
confidence: 84%
“…Alongside the forest maps, we collected a myriad of variables representing the main direct and indirect drivers of forest cover change in Colombia 20,39 , and on tropical deforestation more broadly 22 . For instance, Armenteras et al 20 and Ayram et al 39 identified some of the 'traditional' drivers (roads, population, elevation, slope, etc.…”
Section: Model Input Data Sourcesmentioning
confidence: 99%
“…Alongside the forest maps, we collected a myriad of variables representing the main direct and indirect drivers of forest cover change in Colombia 20,39 , and on tropical deforestation more broadly 22 . For instance, Armenteras et al 20 and Ayram et al 39 identified some of the 'traditional' drivers (roads, population, elevation, slope, etc. ), whereas Murad and Pearse 40 as well as Davalos et al 41 highlighted the role of agriculture (cattle ranching), and others identified more Colombia-specific drivers such as coca cultivation 9,41 , illegal mining and oil pipelines 42 .…”
Section: Model Input Data Sourcesmentioning
confidence: 99%